Contributions to the millipede genus Nepalella Shear, 1979 from China, with four new species and first results on phylogeny based on DNA-barcoding (Diplopoda, Chordeumatida, Megalotylidae) - Liu, Weixin; Wesener, Thomas; Golovatch, Sergei; Tian, Mingyi (Zootaxa, 2017)
Four new species of the chordeumatidan millipede genus Nepalella Shear, 1979, family Megalotylidae, are described from caves in southern China: N. troglodytes sp. nov., N. lobata sp. nov., N. jinfoshan sp. nov., and N. wangi sp. nov. Three of them (except N. lobata sp. nov.) are presumed troglobites. Additional locality records of two cave congeners, N. caeca Shear, 1999 and N. grandoides Golovatch, Geoffroy & Mauriès, 2006, are also provided. DNA-barcoding based on the COI mitochondrial gene is documented in this genus and for species of the order Chordeumatida outside Europe for the first time. Interspecific p-distances between Nepalella species amount to 8.5–15.9%, while intraspecific p-distances are 0–6.8%. The species of Nepalella are found to show a surprisingly low genetic distance from the European genus Atractosoma Fanzago, 1876, family Craspedosomatidae Gray in Jones, 1843, potentially based on the very limited number of barcoding sequences of the order Chordeumatida being available.